The Influence of Halal Lifestyle, Halal Awareness, and Halal Branding on Cosmetic Product Purchase Decisions (A Study on FEBI Students at IAIN Parepare) - Muhammad Farsyal Yuzagautama; Syahriyah Semaun; Islamul Haq; St. Aminah; Damirah Damirah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the influence of Halal Lifestyle, Halal Awareness, and Halal Branding on cosmetic product purchasing decisions among university students in Parepare City. Using a quantitative method with an associative approach, this study explores how these three factors influence the purchasing decision-making process. Data were collected from 96 university students and analyzed using SPSS software, with validity, reliability, and classical assumption tests to ensure the integrity of the results. The research findings indicate that these three factors have a positive and significant influence on university students' purchasing decisions. Halal Lifestyle, which reflects a lifestyle in accordance with Islamic principles, directly influences the preference for Halal-certified cosmetic products. Halal Awareness, which reflects consumers' knowledge and awareness of a product's Halal status, also significantly influences purchasing decisions. Furthermore, Halal Branding, which focuses on promoting Halal attributes in products, strengthens consumer trust and loyalty. This study emphasizes the importance of integrating Halal values into marketing strategies for companies targeting Muslim consumers, particularly in the growing cosmetics industry.